2007
DOI: 10.1021/ja075139p
|View full text |Cite
|
Sign up to set email alerts
|

External Stimulus-Responsive Supramolecular Structures Formed by a Stilbene Cyclodextrin Dimer

Abstract: Cyclodextrin (CD) based supramolecular complexes have been prepared using a stilbene bis(β-CD) dimer and a ditopic adamantyl guest. The conformation of the stilbene bis(β-CD) dimer in aqueous solutions could be photochemically controlled. The ROESY spectra of the β-CD dimer with the adamantyl dimer showed NOE between the protons of adamantyl moieties and the inner protons of the CD. When the host cyclodextrin dimer was in trans conformation, supramolecular dimers or small assemblies are formed in solutions, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(82 citation statements)
references
References 11 publications
2
79
0
1
Order By: Relevance
“…Complexes with busulfan antercancer agent (Menuel, et al, 2007) Bis-β -cyclodextrin linked with ethylene oxide TOF (DHB), ESI Complexes with adamantane (Bistri, et al, 2007) Bis-β-cyclodextrin linked with stilbene TOF (DHB) For construction of supramolecular structures (Kuad, et al, 2007) β-Cyclodextrin dimers TOF/TOF (DHB) Synthesis by click chemistry (Mourer, et al, 2008) β-CD fatty acid esters MALDI Chain lengths (C4---C14) synthesised by trans-esterification of β-CD by vinyl fatty ester using thermolysin in DMSO (Choisnard, et al, 2007) β-CD linked to azobenzene via PEG linker TOF (DHB) For studies on thermal and photochemical conformation switching ) β-CD linked to Ru(II)-terpyridine TOF Encapsulation by CD. Article in Korean β-CD monoesterified with 3-Forms large aggregates w TOF ith two Glycolipids ((E)-dec-2-enyl)-dihydrofuran-2,5-dione recognition sites Gives blue or green fluorescence depending on solvent (Huo, et al, 2008) CDs with guanidinoalkylamino and aminoalkylamino groups on their primary side Synthesis, characterization and properties TOF (DHB) (Mourtzis, et al, 2008) 5-N-β -Cyclodextrincarboxamide-5-methyl-1-pyrroline N-oxide MALDI Improved spin trapping.…”
Section: Maldi Osw Saponinsmentioning
confidence: 99%
“…Complexes with busulfan antercancer agent (Menuel, et al, 2007) Bis-β -cyclodextrin linked with ethylene oxide TOF (DHB), ESI Complexes with adamantane (Bistri, et al, 2007) Bis-β-cyclodextrin linked with stilbene TOF (DHB) For construction of supramolecular structures (Kuad, et al, 2007) β-Cyclodextrin dimers TOF/TOF (DHB) Synthesis by click chemistry (Mourer, et al, 2008) β-CD fatty acid esters MALDI Chain lengths (C4---C14) synthesised by trans-esterification of β-CD by vinyl fatty ester using thermolysin in DMSO (Choisnard, et al, 2007) β-CD linked to azobenzene via PEG linker TOF (DHB) For studies on thermal and photochemical conformation switching ) β-CD linked to Ru(II)-terpyridine TOF Encapsulation by CD. Article in Korean β-CD monoesterified with 3-Forms large aggregates w TOF ith two Glycolipids ((E)-dec-2-enyl)-dihydrofuran-2,5-dione recognition sites Gives blue or green fluorescence depending on solvent (Huo, et al, 2008) CDs with guanidinoalkylamino and aminoalkylamino groups on their primary side Synthesis, characterization and properties TOF (DHB) (Mourtzis, et al, 2008) 5-N-β -Cyclodextrincarboxamide-5-methyl-1-pyrroline N-oxide MALDI Improved spin trapping.…”
Section: Maldi Osw Saponinsmentioning
confidence: 99%
“…Especially, recent developments in supramolecular chemistry using CDs as a building blocks are extremely remarkable. Various supramolecular structures such as catenanes [10-12], rotaxanes [13-17], polyrotaxanes [18-20] and supramolecular polymers [21-23] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of the research of Harada and coworkers on CD-based supramolecular polymers, Kuad and coworkers [71] constructed a photo-responsive alternating supramolecular copolymer system using a b-CD dimer linked with a stilbene moiety and an adamantane dimer linked with 1,3-bis(4-pyridinium) propane (Scheme 11.19). 2D ROESY NMR studies indicated the formation of supramolecular copolymers for both the b-CD dimers of trans-and cis-stilbene units.…”
Section: Photo-responsive Systemsmentioning
confidence: 99%